IDENTIFICATION OF SUSTAINABLE COASTAL MANAGEMENT WITH A BIOPHILIC APPROACH IN TAMBAH MULYO VILLAGE, SEMARANG CITY - Suwarno Kusweanto, David; Martha Jebatu, Eldisya (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
Coastal areas have various threats that require intervention to increase regional resilience. Resilient coasts are the answer to multiple threats, such as flooding, regulations, maritime economics, and the existence of coastal organizations. Resilient coastal areas are not only about the area’s physical condition but also the coastal regions’ systematic management. One of the coastal areas in Semarang City is Tambak Mulyo. This research aims to comprehensively understand the coastal area management system and physical, regional, and organizational systems. The research data uses primary data, namely a questionnaire with a cluster sampling technique. The research method uses quantitative descriptive analysis to describe the state of management of the Tambak Mulyo coastal area. The research results show that the level of public awareness in RW XII, XIII, XIV and XV is good. People are used to floods, but not all people can adapt well. The organization only exists in RW XV but is less active. This is the case with regulations that already exist in every RW XII, XIII, XIV and XV area, but many people still need to learn the contents of these regulations.